2017
DOI: 10.1016/j.atmosenv.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of volatile organic compounds (VOCs) from vehicular emissions at roadside environment: The first comprehensive study in Northwestern China

Abstract: 21Vehicular emission (VE) is one of the important anthropogenic sources for ground-level volatile 22 organic compounds (VOCs) in both urban and suburban areas. A first comprehensive campaign was 23 conducted at an urban roadside in Xi'an, China in summer, 2016. A total of 57 VOCs, as known as critical 24 surface ozone (O 3 ) precursors, and other trace gases were measured simultaneously during the sampling 25 period. Iso-pentane, a tracer of gasoline evaporation, was the most abundant VOC in the roadside sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(54 citation statements)
references
References 55 publications
4
49
0
1
Order By: Relevance
“…Under atmospheric conditions, the reaction of m/p‐xylene with OH radicals is rapid; thus, the X/E ratio decreases with time (C. Huang, Wang, et al, ). When the value of the X/E ratio is approximately 3, the contribution of VOCs from local emissions is more important (B. Li, Ho, et al, ). The X/E ratio in this study showed no obvious diurnal variation (Figure S4b), with a ratio of 2.2 ± 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…Under atmospheric conditions, the reaction of m/p‐xylene with OH radicals is rapid; thus, the X/E ratio decreases with time (C. Huang, Wang, et al, ). When the value of the X/E ratio is approximately 3, the contribution of VOCs from local emissions is more important (B. Li, Ho, et al, ). The X/E ratio in this study showed no obvious diurnal variation (Figure S4b), with a ratio of 2.2 ± 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…p is the number of source, f and g are the species profile of each source and the amount of mass contributed by each source to the sample e ij is the residual for each sample and specie [22]. The other details of PMF applied to VOC data for source profiles and the contributions of each VOC species have been introduced in previous studies [24][25][26]. In this study, 28 VOC species were input into the PMF model.…”
Section: Pmf Modelmentioning
confidence: 99%
“…The ratios between the mixing ratios of pairs of ambient VOC species are useful indictors of the major emission sources, photochemical process and the influence of the generating functions. The ratio of ambient mixing ratios of two hydrocarbons with similar chemical reactivity are theoretically equal to those of their relative emission rates from sources [26,34]. Thus, we examined the monthly variations in several groups of VOC species ratio to reveal the typical characteristics of different emissions.…”
Section: Correlations Between Voc Speciesmentioning
confidence: 99%
“…1. Improvement of engines is carried out to ensure the most complete combustion of fuel [21,22]. The engines based on weakest mixture, multi-valve system of redistribution, fuel injection instead of carbureted air-fuel mixture, electronic ignition.…”
Section: Measures For Reduction the Environmental Impact Of Transportmentioning
confidence: 99%